Differences in Mathematics Concept Understanding Ability And Learning Independence of Students Reached with Discovery Learning and Cooperative Learning Model Type of Group Investigation at SMK Multi Karya - Purba, Putri Anggraini; Sitompul, Pardomuan; Napitupulu, E Elvis (Universitas PGRI Madiun, 2023)
: To find out the characteristics and advantages supported by data from previous research, which shows that learning with discovery and cooperative learning models of group investigation type can improve students' ability to understand mathematical concepts and independent learning. The findings obtained several conclusions related to implementing learning using the discovery learning model and the group investigation learning model on differences in the ability to understand mathematical concepts and student learning independence at SMK Multi Karya.